SURVEY KONDISI DAN PELESTARIAN NASKAH KUNO DI MUSEUM SIGINJAI PROVINSI JAMBI - Damaji Ratmono (Perpustakaan Nasional RI, 2017)
The richness of Indonesian culture in the form of ancient manuscripts needs to be preserved properly in order to be used for present and future generations. The ancient manuscripts in the Museum Siginjai in Jambi Province are no exception. The existence of manuscripts in the Museum Siginjaiis a cultural heritage that has noble values that reflect the life of the people of Jambi Province in the past. Based on a survey of condition conducted by the author and the team of conservator of library material of National Library, various types of damage were found in those ancient manuscripts in the museum; such as fragile papers, broken binding texts, and manuscripts unprotected by protective box. Accordingly, techniques to improve the manuscripts by using mending or patching and connecting techniques, manual lamination techniques, binding techniques, and the manufacture of protective I portepel boxes were conducted. With a variety of techniques that were conducted precisely, effectively, and efficiently some of broken manuscripts in Museum Siginjai could be repaired and preserved so as to benefit the present and future generations